Review of Corrosion of Carbon Steel in CO2 – Containing Environment of the Oil and Gas Industry: Mechanism Understanding to Prediction Mode - Chowwanonthapunya, T.; Peeratatsuwan, C.; Suphamitmongkol, W. (Journal of Advanced Development in Engineering and Science, 2023)
CO2 corrosion has been known as one of the major mode of failure in a lot of the steel process equipment of hydrocarbon production all over the world. Hence, the comprehensive understanding of CO2 corrosion is essential to establish the robust design, operations and integrity of the hydrocarbon production process. This paper highlights the modern understanding of CO2 corrosion mechanisms for steels used in oil and gas production. The special attention is also paid to the important parameters affecting the protectiveness of steel under the attack of CO2 corrosion. Besides, the empirical model for practical engineering application to predict the rate of this specific damage is also presented.